Patterns of economic change in the south‐west during the fifteenth century: evidence from the reductions to the fifteenths and tenths1. (27th September 2016) - Forrest, Mark
Abstract : The fifteenth century rebates to the fifteenth and tenth form a large body of evidence which has rarely been used to assess economic change. They were set by local commissioners who employed their knowledge of the conditions within their counties. In many cases the commissioners can be demonstrated to have applied the reductions in a thoughtful and proportionate manner, often revealing local economic conditions. There is considerable variation in their application between counties and their use is greatly enhanced when compared with other sources.